OFDM SYSTEMS BASED ON INTER CARRIER INTERFERENCE WITH ASB - R.RAVI; N. SUTHANTHIRA VANITHA (Innovare Journal of Engineering and Technology, 2013)
In this paper Orthogonal frequency division multiplexing based wireless systems are spectrally efficient and it is being increasingly used in high data rate wireless communication systems, but they are vulnerable to inter carrier interference (ICI). The signal strength varies due to different individual path loss and also due to different amount of Doppler spread because of their independent velocities. Therefore, the ICI among to combat ICI are towards using synchronization and interference cancellation. In this paper we use adaptive sub carrier bandwidth(ASB) along with adaptive bit loading to mitigate ICI in such conditions, which will keep receiver design very simple and it keeps maximum throughput and minimum BER in each situation. Results show that ASB can provide higher throughput than fixed sub carrier bandwidth.